Čitalništvo v perspektivi družbenogeografskih dejavnikov - Perenič, Urška (Slavistična revija, 2012)
This article presents various factors, aside from national-political impetuses, that may have significantly influenced the formation of a reading societies network in the ethnically Slovene territory in the 1860s. It speculates on the nature of the connections between these factors and the organization of reading centers' spatial distribution in the territory. The article attempts to reveal the nature of the interaction between the demographic features of specific population centers and broader administrative divisions in the context of which the reading movement developed. In so doing, it relies on the first comprehensive Austro-Hungarian census, which was completed in 1869. Among the factors, special attention is devoted to the administrative and judicial organization of regions with reading centers, their local administrative divisions, and the distribution of educational infrastructure made up of middle and high schools. On these bases, the article offers several possible models that show how the factors inquestion were interconnected in the rise and spread of reading centers throughout the ethnically Slovene territory.
Keywords: 19.st.; 19th century; administrative organization; čitalništvo; demografija; demography; judicial organization; reading centers; school; schools; Slovenci; Slovenes; Slovenians; sodstvo; šolstvo; uprava